Cytokine adsorption in patients with acute-on-chronic liver failure (CYTOHEP): a single center, open-label, three-arm, randomized, controlled intervention trial - Sekandarzad, Asieb; Weber, Enya; Prager, Eric Peter; Graf, Erika; Bettinger, Dominik; Wengenmayer, Tobias; Supady, Alexander (Trials, 2022)
Liver cirrhosis is a major healthcare problem and the mortality rate is high. During recent years, systemic inflammation has been recognized as a major driver of hepatic decompensation and progression of liver cirrhosis to acute-on-chronic liver failure (ACLF). The aim of the CYTOHEP study is to assess the impact of extracorporeal hemoadsorption with the CytoSorb adsorber on serum bilirubin concentrations, humoral inflammation parameters, liver function parameters, and patient survival in patients with ACLF and acute kidney injury (AKI).